Polymicrobial Candida biofilms: friends and foe in the oral cavity. Issue 7 (15th September 2015) - O'Donnell, Lindsay E.; Millhouse, Emma; Sherry, Leighann; Kean, Ryan; Malcolm, Jennifer; Nile, Christopher J.; Ramage, Gordon
Abstract : The role of polymicrobial biofilm infections in medicine is becoming more apparent. Increasing number of microbiome studies and deep sequencing has enabled us to develop a greater understanding of how positive and negative microbial interactions influence disease outcomes. An environment where this is particularly pertinent is within the oral cavity, a rich and diverse ecosystem inhabited by both bacteria and yeasts, which collectively occupy and coexist within various niches as biofilm communities. Studies within this environment have however tended to be subject to extensive independent investigation, in the context of either polymicrobial bacterial communities or yeast biofilms, but rarely both together. It is clear however that they are not mutually exclusive. Therefore, this review aims to explore the influence of candidal populations on the composition of these complex aggregates and biofilm communities, to investigate their mechanistic interactions to understand how these impact clinical outcomes, and determine whether we can translate how this knowledge can be used to improve patient management. Abstract : An examination of where and how Candida interacts with bacteria in the oral cavity Abstract :